Does bilingual experience affect early visual perceptual development? - Schonberg, Christina; Sandhofer, Catherine M.; Tsang, Tawny; Johnson, Scott P. (Frontiers in Psychology, 2014)
Visual attention and perception develop rapidly during the first few months after birth, and these behaviors are critical components in the development of language and cognitive abilities. Here we ask how early bilingual experiences might lead to differences in visual attention and perception. Experiments 1-3 investigated the looking behavior of monolingual and bilingual infants when presented with social (Experiment 1), mixed (Experiment 2), or nonsocial (Experiment 3) stimuli. In each of these experiments, infants’ dwell times (DT) and number of fixations to areas of interest (AOIs) were analyzed, giving a sense of where the infants looked. To examine how the infants looked at the stimuli in a more global sense, Experiment 4 combined and analyzed the saccade data collected in Experiments 1-3. There were no significant differences between monolingual and bilingual infants’ DTs, AOI fixations, or saccade characteristics (specifically, frequency and amplitude) in any of the experiments. These results suggest that monolingual and bilingual infants process their visual environments similarly, supporting the idea that the substantial cognitive differences between monolinguals and bilinguals in early childhood are more related to active vocabulary production than perception of the environment.